2016
DOI: 10.1007/s11829-016-9415-2
|View full text |Cite
|
Sign up to set email alerts
|

The constitutive expression and induction of three β-1,3-glucanases by bird cherry-oat aphid in relation to aphid resistance in 15 barley breeding lines

Abstract: In this study, 15 closely related barley genotypes were analyzed for the abundance of three b-1,3-glucanase transcripts immediately before and during infestation by the bird cherry-oat aphid (Rhopalosiphum padi L.). The barley lines are doubled haploid lines in backcross (BC) generations BC1 and BC2 from a cross between cultivar Lina and a wild barley accession. Previously, they have been characterized as susceptible (S) or resistant (R) to R. padi based on their ability to support nymphal growth. Here we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…However, plant traits may influence not only aphid physiology but also aphid behavior. Mehrabi et al ( 2016 ) found that aphid settling rate of apterous aphids confined for 2 days with selected lines from this breeding material was lower on resistant than susceptible genotypes in those cases where there were significant differences between such lines. This indicates that plant resistance traits influence host acceptance, which in turn may influence food intake, aphid growth and reproduction of successive aphid generations in the field.…”
Section: Discussionmentioning
confidence: 83%
“…However, plant traits may influence not only aphid physiology but also aphid behavior. Mehrabi et al ( 2016 ) found that aphid settling rate of apterous aphids confined for 2 days with selected lines from this breeding material was lower on resistant than susceptible genotypes in those cases where there were significant differences between such lines. This indicates that plant resistance traits influence host acceptance, which in turn may influence food intake, aphid growth and reproduction of successive aphid generations in the field.…”
Section: Discussionmentioning
confidence: 83%
“…It is much more logical; therefore, that callose breakdown is facilitated by upregulation of plant glucanases (Van der Westhuizen et al, 1998) probably making use of salivary effectors. In keeping with this idea, infestation with R. padi induced a transcript abundance of three β-1,3-glucanases in 15 barley breeding lines (Mehrabi et al, 2016). In Mp55-expressing Arabidopsis plants, callose deposition in response to aphid infestation is reduced (Elzinga et al, 2014), but the molecular action of Mp55 is yet to be identified.…”
Section: Functional Aspects Of Salivary Proteinsmentioning
confidence: 77%
“…To investigate aphid-induced responses, five genes were studied: CI2c , thionin proprotein-processing enzyme ( TPPE ) [ 48 ], a subtilisin-like serine endoprotease, hordolisin [ 49 ], allene oxide synthase ( AOS ) and a β -1,3-glucanase [ 50 ]. The genes are induced similarly by BCA and GPA ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Their expression was stable or suppressed by aphids in the transgenic lines, when compared to control or resistant plants ( Fig 4 ). As a putative positive factor, we considered a β -1,3-glucanase, suggested as a susceptibility factor towards BCA [ 50 ]. In our study, it was induced by aphids at the highest transcript levels in the CI2c 6–4 transgenic line ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%